PENGUJIAN MACAM DIODE DAN URINE KELINCI : UPAYA PENINGKATAN KUALITAS DAN HASIL TANAMAN KAILAN (Brassica alboglabra L.) DENGAN IMPLEMENTASI TEKNOLOGI SIPLO - anggy twodestria cahayaningrum; Sugiarto Sugiarto; Indiyah Muwarni (AGRONISMA, 2021)
Kailan is a popular type of leaf vegetable because it has advantages compared to mustard greens, namely the leaves are thicker, green, tastes good, legit, sweet and tender and raises consumer interest, which is high, namely 287.30 kw/ha in 2005 and decreased to 253.70 kw. /ha in 2006 so that there is a need for adequate agricultural cultivation technology among farmers. This study aims to determine the effect of diode and rabbit urine on the quality and yield of kailan plants. This study used a factorial randomized block design (RAK) with controls. Factor 1 is Diode (D1) : Iron ; (D2) : Copper ; (D3) : Aluminum. Factor 2 Rabbit Urine (U1) : 50 ml/L ; (U2) : 100 ml/L ; (U3) : 150 ml/L. Data analysis using analysis of variance BNJ test 5% and Dunnet test 5%. The results showed that there was a significant interaction between the diode and the administration of rabbit urine POC on the weight value variable consumed to obtain results in the treatment of D2U2 (Copper Diode + 100 ml Rabbit Urine POC), D2U3 (Copper Diode + 150 ml Rabbit Urine POC) and D3U2 (Aluminum Diode). + 100 ml POC Rabbit Urine) showed significantly different results. The variable quality of Total Dissolved Solids showed that the copper diode treatment showed significant results, namely D2 (Copper) = 5.62 getting the best results as well as U2 (100 ml/L POC Rabbit Urine) = 5.76. The weight variable per hectare showed significant results with the highest value of D2 (Copper) = 0.48.